Effect of Longtime Sheath Current on Insulation Screen of 115kV XLPE Underground Cable - K. Jariyanurat; Siwakorn Jeenmuang; Patt Udomluksananon; Sittipong Kerdmanee; Sakda Lacharochana; Norasage Pattanadech (My University, 2024)
Due to the need to extend the life of underground cables that are universally installed and used in power plants in Thailand, The life assessment must be concerned with advanced techniques, both chemical and physical, exactly. The components that needed to be analyzed were divided into two main groups: the insulation and physical systems. One of the most requisites is pyrolysis. Pyrolysis can occur in the underground cable system with many factors, for instance, the ambient temperature, overload, loss of connector, and longtime sheath current. Thus, this paper described the effect of the longtime sheath current on the insulation screen of 115kV XLPE underground power cable. Sheath current that ran into the system for longtime effectively effected to the insulation screen by destroying the structure of chemical properties leading to the short lifetime and getting the high risk to breakdown with the continue use.
Keywords: Thermal Analysis in Power Transmission; High voltage insulation and dielectric phenomena; Power Line Inspection Robots